RETRACTED ARTICLE:. WAYS TO IMPROVE TREATMENT EFFICIENCY OF PATIENTS WITH HIGH CARDIOVASCULAR RISK - G. A. Baryshnikova; S. A. Chorbinskaya; I. J. Stepanova (Евразийский Кардиологический Журнал, 2015)
Retracted 11.11.2019To reduce the overall cardiovascular risk it is advisable to use a combination of drugs - the poly-pill that will increase the effectiveness of therapy and patient compliance. The company «Gedeon Richter» has created a polypill - the Ekvamer medication, which in addition to amlodipine and lisinopril includes rosuvastatin - one of the most powerful and safe statins to date that will provide hosting and primary and secondary prevention of cardiovascular diseases and their complications.